HUBUNGAN KUALITAS PRODUK, KUALITAS PELAYANAN, DAN LOKASI DENGAN KEPUTUSAN PEMBELIAN PRODUK DI ETHAN COFFEE AND SPACE - Eva Novi Triana; Miracle Triswardani Putri; Lintang Kusuma Ramdhani; Pakidah Umi Nurhidayah; Marjam Desma Rahadhini (Politeknik Bisnis Indonesia, 2024)
Abstract This study seeks to establish the correlation between product quality, service quality, and location with the purchase behavior of customers at Ethan Coffee and Space. The research utilizes a quantitative questionnaire as the data gathering strategy. The participants were chosen through random sampling, with a sample size of 56 individuals who are patrons of Ethan Coffee and Space. The employed data analysis technique is Spearman Rank Correlation analysis. The research findings indicate that there is a notable and favorable correlation between product quality and purchase decisions, with a high degree of association. The quality of service exhibits a substantial and favorable correlation, demonstrating a high level of association with purchasing decisions. The location exhibits a substantial and favorable correlation, and demonstrates a modest degree of association with purchasing decisions.